Brain collection, standardized neuropathologic assessment, and comorbidity in ADNI participants - Franklin, Erin E. (Alzheimers Dement, 2015)
INTRODUCTION: The Alzheimer’s Disease Neuroimaging Initiative Neuropathology Core (ADNI-NPC) facilitates brain donation, ensures standardized neuropathologic assessments, and maintains a tissue resource for research. METHODS: The ADNI-NPC coordinates with performance sites to promote autopsy consent, facilitate tissue collection and autopsy administration, and arrange sample delivery to the NPC, for assessment using NIA-AA neuropathologic diagnostic criteria. RESULTS: The ADNI-NPC has obtained 45 participant specimens and neuropathologic assessments have been completed in 36 to date. Challenges in obtaining consent at some sites have limited the voluntary autopsy rate to 58%. Among assessed cases, clinical diagnostic accuracy for Alzheimer disease (AD) is 97%; however, 58% show neuropathologic comorbidities. DISCUSSION: Challenges facing autopsy consent and coordination are largely resource-related. The neuropathologic assessments indicate that ADNI’s clinical diagnostic accuracy for AD is high; however, many AD cases have comorbidities that may impact the clinical presentation, course, and imaging and biomarker results. These neuropathologic data permit multimodal and genetic studies of these comorbidities to improve diagnosis and provide etiologic insights.